(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2016)
يتعرض الكادر التمريضي إلى مشاكل عضلية هيكلية مرتبطة بالعمل أثناء تقديم الرعاية التمريضية وذلك بسبب الممارسة الخاطئة لميكانيكية الجسم , هدفت هذه الدراسة إلى تقييم مستوى معلومات الكادر التمريضي حول استخدام ميكانيكية الجسم و مدى استخدامهم لميكانيكية الجسم ضمن الأنشطة التمريضية,أجريت هذه الدراسة على عينة مؤلفة من (65) ممرضة في أقسام الجراحة والداخلية والعناية المركزة في مشفى الأسد الجامعي حيث تم مقابلة كل ممرضة على حدا وتم تقييم معلوماتهن عن طريق استمارة تقييم المعلومات ثم تم تقييم مدى استخدامهن لميكانيكية الجسم ضمن أنشطة محددة في الرعاية التمريضية باستخدام قائمة الملاحظة , وخلصت الدراسة إلى نتيجة مفادها إن مستوى معلومات وممارسات الكادر التمريضي حول ميكانيكية الجسم تراوحت بين الضعيف والمتوسط , وأوصت الدراسة بضرورة رفع مستوى معلومات وممارسات الكادر التمريضي حول ميكانيكية الجسم الجيدة عن طريق البرامج التدريبية والتعليمية والمحاضرات . Nursing staff exposed to musculoskeletal problems associated with work while providing nursing care because of the erroneous practice of mechanical body, This study aimed to assess the level of nursing staff information about the use of mechanical body and the extent of their use of mechanical body within the nursing activities ,This study was conducted on the author of a sample of 65 nurse in surgery and internal and intensive care at University Hospital Assad where he was interviewed every nurse on the end were evaluated their knowledge by assessing information form was then assess how their use of body mechanics within specific activities in nursing care using the observational checklist , the study concluded that the level of information and practices of nursing staff about mechanical body ranged between poor and average, the study recommended the need to raise the level of information and practices of nursing staff about good mechanical body through training and educational programs and lectures.